Travellers with disabilities: a substantial and growing tourism niche market - Robinson, Neil; Carter, M.; Packer, Tanya; Goddard, Trevor; Muir, Tegan. (CAUTHE, 2007)
Providing tourism services to specific niche markets can broaden a business's customer base bringing about a sustainable competitive advantage. An emerging but largely under serviced tourism consumer group is the accessible tourism niche. This paper begins comparing the backpackers', seniors', and gay and lesbian markets to establish if parallels in their development, growth and consumer needs can be observed. The argument is then presented for accessible tourism, not only looking at the social and legal imperatives for servicing this market but also some of the more recent statistics to highlight it's financial worth. As part of this review, a discussion of the ongoing and discouraging barriers to greater participation is undertaken with a view to making recommendations for future action.The review revealed similarities between the early adoption of the accessible tourism niche across each of the three groups. Overlap was also found in the requirements of the groups, for example, seniors, who are increasingly likely to experience disability with aging increasing the need for accessible tourism services. Quite aside from any social or legal imperative, the increasing value and size of the accessible tourism niche strongly suggests this is a largely untapped market worthy of greater managerial attention and research effort. The discussion contained here is timely given that many discouraging barriers and service quality issues remain which exclude people with disabilities from a full range of tourism experiences.